Analyzing Experiences, Prevention and Treatment of Bullying At Schools - Hambali Hambali; Al Rafni; Jumili Arianto; Hariyanti Hariyanti (Universitas of Muhammadiyah Makassar, 2023)
This research is motivated by the problem of rampant cases of bullying that occur in schools. Therefore, this study aims to describe the experiences of students related to bullying behavior at school and future efforts to prevent and overcome bullying behavior. This research uses a qualitative design with descriptive methods. The study was conducted in SMA / SMK Dumai City by involving school students and teachers in June-August 2023. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis techniques use the Miles and Huberman model, consisting of data collection, verification and reduction, and conclusion drawing. The triangulation technique uses data source triangulation. The results showed that (1) the bullying experience experienced by students generally occurred verbally. Their attitudes in responding to bullying are also different; some are ignorant and ignore the bullying received, sad and keep it to themselves, but some report to parents and BK (counseling guidance) teachers at school; (2) Efforts to prevent bullying behavior at school are carried out in the form of appeals, socialization, infiltration in subjects through planting about manners and ethics in getting along; (3) As for handling efforts if bullying occurs at school, it will be processed first by the subject teacher or vice-grade. Furthermore, coaching is carried out by the school's counseling teacher or deputy student affairs. The understanding of bullying behavior is quite good in students, which is marked by their ability to identify bullying behavior based on experience and realize that bullying behavior is an act of violation of human rights (HAM). Still, the school needs to maximize the action of preventing and handling bullying behavior. Therefore, synergy is needed between students and schools to minimize bullying behavior in schools.